Spirit Animals: Wild Born - Book 1 - Mull, Brandon 1974- (New York, NY : Scholastic Inc., 2013)
As a dark force engulfs the land, the fate of Erdas has fallen on the shoulders of four young strangers who each have forged a rare bond with their spirit beasts -- a bond that gives great powers to all of them.
Keywords: Human-animal relationships -- Juvenile fiction; Good and evil -- Juvenile fiction; Shapeshifting -- Juvenile fiction; Human-animal relationships -- Fiction; Good and evil -- Fiction; Shapeshifting -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Adventure stories; Fantasy fiction